Efficient Bayesian inference for multiple change-point and mixture innovation models - Paolo Giordani; Robert Kohn (Sveriges Riksbank, 2006)
Time series subject to parameter shifts of random magnitude and timing are commonly modeled with a change-point approach using Chib's (1998) algorithm to draw the break dates. We outline some advantages of an alternative approach in which breaks come through mixture distributions in state innovations, and for which the sampler of Gerlach, Carter and Kohn (2000) allows reliable and efficient inference. We show how this approach can be used to (i) model shifts in variance that occur independently of shifts in other parameters (ii) draw the break dates efficiently in change-point and regime-switching models with either Markov or non-Markov transition probabilities. We extend the proofs given in Carter and Kohn (1994) and in Gerlach, Carter and Kohn (2000) to state-space models with system matrices which are functions of lags of the dependent variables, and we further improve the algorithms in Gerlach, Carter and Kohn by introducing to the time series literature the concept of adaptive Metropolis-Hastings sampling for discrete latent variable models. We develop an easily implemented adative algorithm that promises to sizably reduce computing time in a variety of problems including mixture innovation, change-point, regime-switching, and outlier detection.
Keywords: C11; C15; C22; 330; Structural breaks; Parameter instability; Change-point; State-space; Mixtures; Discrete latent variables; Adaptive Metropolis-Hastings; New-Keynesian Phillips Curve; Kleine offene Volkswirtschaft; Inflation; Momentenmethode; Theorie; Schweden